Population Education in India: A Perspective - Sharma, Ms. Garima (IJRDO- Journal of Educational Research, 2018)
One of the formidable problems which stare us in the faces, is our rapid increasing population, which offsets every endeavour for development. A need is being felt for imparting factual knowledge about population dynamic, so that the younger generation may understand the nature and magnitude of the burden imposed by rapid population growth.Our population is increasing annually at a rapid rate of 2.5 percent India is next to China, has little less then three times the population of U.S.A., twenty-one times the population of Canada and more than six times the population of Japan. With the present growth rate the country’s population may reach the incredible figure of one-billion before the end of this century